Monitoring of Fruit Flies (Diptera: Tephritidae) on Cucurbit Vegetables in Sindhuli, Nepal - Bhusal, N.R.; Kafle, K.; Bhattarai, S.S.; Adhikari, D. (Journal of the Plant Protection Society, 2020)
Abstract available with full text.